Attitudes towards the adaptation of foreign personal names - Eduardo Tadeu Roque Amaral (Nordisk Tidskrift för Socioonomastik, 2025)
This study examines the attitudes of a group of native Spaniards towards aspects concerning the necessity of adapting foreign names to the official languages of the country and towards the legal regulations governing name assignment and modification. The research adopts theoretical principles from socio-onomastics and linguistic attitude analysis, also incorporating social and anthropological concepts. Data were collected in person through interviews conducted in the city of Salamanca during April and May 2023. This study analyses the responses of 40 participants, stratified by gender (male and female) and age group (18–29 years; 30–45 years; 46–64 years; 65 and older). In general, the results indicate a recognition of names as an identity sign that the state should acknowledge and respect. Nevertheless, it is possible to observe both agreements and disagreements regarding the adaptation of names, as well as the influence of the social factor of age on attitudes.